Application of bone marrow samples for discrimination of acute promyelocytic leukemia from other types of acute leukemia using the routine automated hematology analyzer. (10th January 2014) - Jang, M. J.; Choi, H. W.; Lee, S. Y.; Lee, O. J.; Kim, H. R.; Shin, J. H.; Suh, S. P.; Ryang, D. W.; Shin, M. G.
Summary Introduction Unreported parameters produced by automated blood cell counter, particularly large unstained cells (LUC) and delta neutrophil index (DNI), indicated the presence of immature and possibly abnormal cell populations in white blood cell population. The purpose of this study was to investigate the laboratory performance for discrimination of acute promyelocytic leukemia (APL) cells from other types of leukemia cells and clinical value of LUC and DNI parameters in bone marrow (BM) samples of patients with acute leukemia. Methods A total of 73 BM samples of patients with various type of acute leukemia were analyzed. LUC and DNI parameters were determined by an automated hematology analyzer (ADVIA 120; Siemens Healthcare Diagnostics, New York, NY, USA). Statistical analysis was performed using Kruskal–Wallis and Mann–Whitney U methods. Receiver operating characteristic curve (ROC) analysis, survival analysis, and Cox proportional hazard model were used to evaluate the clinical implication. Results There were significant differences (P < 0.05) between APL group and other group in the DNI and LUC values except for DNI between APL group and non‐APL myeloid leukemia group. The area under curve of LUC was larger than that of DNI from the ROC analysis for discrimination between APL group and other group. High LUC value was associated with the increased risk of adverse outcomes and the worse overall survival in patients with acute leukemia. Conclusion Delta neutrophil index and LUC in BM showed discriminating power of APL cells from other leukemia cells.